Chitosan-Based Multifunctional Biomaterials as Active Agents or Delivery Systems for Antibacterial Therapy - Meng Wang; Yue Wang; Geyun Chen; Hongyu Gao; Qiang Peng (Bioengineering)
Antibiotic therapy has been a common method for treating bacterial infections over the past century, but with the rise in bacterial resistance caused by antibiotic abuse, better control and more rational use of antibiotics have been increasingly demanded. At the same time, a journey to explore alternatives to antibiotic therapies has also been undertaken. Chitosan and its derivatives, materials with good biocompatibility, biodegradability, and excellent antibacterial properties, have garnered significant attention, and more and more studies on chitosan and its derivatives have been conducted in recent years. In this work, we aim to elucidate the biological properties of chitosan and its derivatives and to track their clinical applications, as well as to propose issues that need to be addressed and possible solutions to further their future development and application.